2009
DOI: 10.1177/030089160909500306
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of Acute Myeloid Leukemia in the General Population: Data from Southern Switzerland

Abstract: Most patients with acute myeloid leukemia are older than 60 years, and their outcome is still disappointing. For younger patients, the prognosis is better if they receive high-dose cytarabine as post-remission therapy and if they are treated in the setting of a clinical trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 32 publications
(41 reference statements)
0
21
0
Order By: Relevance
“…1 A few population-based studies have reported 3-year survival rates of only 9-10% and 5-year survival of 3-8% in patients aged 60 years and older, compared with 5-year survival rates of up to 50% for younger patients. [2][3][4] This poor survival reflects the higher frequency in older patients of poor prognostic factors and comorbidities, as well as a preference among physicians not to treat older patients as aggressively because of the expectation that they are less likely to benefit from intensive therapies. 5 Despite the paucity of clinical studies evaluating different treatment options in older AML patients, 6 there is some evidence available on treatment practices and associated outcomes in older AML patients.…”
Section: Introductionmentioning
confidence: 99%
“…1 A few population-based studies have reported 3-year survival rates of only 9-10% and 5-year survival of 3-8% in patients aged 60 years and older, compared with 5-year survival rates of up to 50% for younger patients. [2][3][4] This poor survival reflects the higher frequency in older patients of poor prognostic factors and comorbidities, as well as a preference among physicians not to treat older patients as aggressively because of the expectation that they are less likely to benefit from intensive therapies. 5 Despite the paucity of clinical studies evaluating different treatment options in older AML patients, 6 there is some evidence available on treatment practices and associated outcomes in older AML patients.…”
Section: Introductionmentioning
confidence: 99%
“…Among the other variables, age has proved to be an important prognostic factor in many studies (4,(22)(23)(24)(25). In addition, AML with multilineage dysplasia has been associated with a poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Most series of older patients with newly diagnosed AML have noted CR rates between 40 and 60 percent [2,4,5,8,12,[17][18][19][20][21]. While suitably selected older patients given aggressive induction therapy may achieve CR at a rate approximating that of younger patients [12], others may spend a significant proportion of their remaining life in a hospital setting receiving treatment.…”
Section: Outcomes In Older Compared To Younger Patientsmentioning
confidence: 99%